EFEKTIVITAS PENGGUNAAN CELEBRITY DIPLOMACY BTS (BANGTAN SONYEONDAN) SEBAGAI GOODWILL AMBASSADOR UNICEF DALAM MELAKUKAN KAMPANYE ANTI-KEKERASAN “LOVE MYSELF” - Eny Wahyuni; Lalu Puttrawandi Karjaya; Valencia Husni (Indonesian Journal of Global Discourse, 2023)
Violence against children is a big problem that still often occurs in all parts of the world, both online violence (cyberbullying) and violence that occurs in person. One of UNICEF’s efforts to solve the issue is by initiating celebrity diplomats, namely BTS, to cooperate with UNICEF in the anti-violence Campaign against children "Love Myself". This study aims to explore the role of non-state actors, in this case, celebrities as diplomatic figures who have a significant role in Campaigning for the issue of anti-violence against children. This study uses the concept of Celebrity Diplomacy, the concept of International Organization, and the theory of Regime Effectiveness. This qualitative descriptive research uses secondary data derived from multiple sources and analyzed through the model of Miles and Huberman. The results of this study indicate that the Love Myself Campaign is effective in spreading positive messages to love yourself and decreasing the amount of violence against children, and has succeeded in raising many funds from various work programs or activities initiated by UNICEF with BTS, which will be used entirely for the needs of the Campaign.